Comparison of the effects of antihypertensive agents on central blood pressure and arterial stiffness in isolated systolic hypertension - Mackenzie, Isla S; McEniery, Carmel M; Dhakam, Zahid; Brown, Morris J; Cockcroft, John R; Wilkinson, Ian B (Hypertension (Dallas, Tex. 1979), 2009)
Isolated systolic hypertension is an important risk factor for cardiovascular disease and results primarily from elastic artery stiffening. Although various drug therapies are used to lower peripheral blood pressure (BP) in patients with isolated systolic hypertension, the effects of the 4 major classes of antihypertensive agents on central BP, pulse pressure (PP) amplification, and arterial stiffness in this condition are not clear. Fifty-nine patients over the age of 60 years with untreated isolated systolic hypertension (systolic BP > or =140 mm Hg and diastolic BP <or =90 mm Hg) were randomly assigned to receive 1 of the following 4 antihypertensive agents: perindopril, atenolol, lercanidipine, or bendrofluazide. BP was measured using a mercury sphygmomanometer, and augmentation index and carotid-femoral (aortic) pulse wave velocity were measured at baseline, after 2 weeks of placebo therapy, and at the end of 10 weeks of active therapy. Peripheral systolic BP and peripheral PP were reduced similarly after treatment with all 4 classes of drug. However, central PP was only reduced significantly by perindopril, lercanidipine, and bendrofluazide, whereas atenolol had no effect. Lercanidipine reduced the augmentation index, whereas atenolol increased it. Aortic pulse wave velocity was not changed by any of the drugs. In summary, despite similar reductions in peripheral systolic and PPs with the 4 classes of drug, changes in central pressure and augmentation index varied. Because central PP and increased wave reflections are considered important risk factors in patients with isolated systolic hypertension, the choice of therapy may be influenced by these findings in the future.